2021
DOI: 10.3390/cells10123316
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Hypoxic Signaling and Oxidative Stress via the MicroRNA–SIRT2 Axis and Its Relationship with Aging-Related Diseases

Abstract: The sirtuin family of nicotinamide adenine dinucleotide-dependent deacetylase and ADP-ribosyl transferases plays key roles in aging, metabolism, stress response, and aging-related diseases. SIRT2 is a unique sirtuin that is expressed in the cytosol and is abundant in neuronal cells. Various microRNAs were recently reported to regulate SIRT2 expression via its 3′-untranslated region (UTR), and single nucleotide polymorphisms in the miRNA-binding sites of SIRT2 3′-UTR were identified in patients with neurodegene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 123 publications
0
7
0
Order By: Relevance
“…Members of sirtuin family play the key role in aging and age-related disease ( Kaitsuka et al, 2021 ). In the present study, GRb1 could increase the protein levels of SIRT1, SIRT3, SIRT6, and SIRT7 in the small intestines of old mice.…”
Section: Discussionmentioning
confidence: 99%
“…Members of sirtuin family play the key role in aging and age-related disease ( Kaitsuka et al, 2021 ). In the present study, GRb1 could increase the protein levels of SIRT1, SIRT3, SIRT6, and SIRT7 in the small intestines of old mice.…”
Section: Discussionmentioning
confidence: 99%
“…The role of SIRTs in EC senescence was also explored in human retinal microvascular ECs (HRECs), where again it was shown that glucose-induced oxidative stress downregulated SIRTs (SIRT3, 4, 5) in vitro and in vivo , increased SIRT-targeting miRNAs and led to early HREC senescence, endothelial-to-mesenchymal transition, and oxidative damage contributing to aging (Liu et al, 2020 ). However, not all SIRTs share the same role, for example SIRT2 was shown to have opposite effects to SIRT1 in the stress response pathway, age-related diseases, and aging (Outeiro et al, 2007 ; Wang Y. et al, 2020 ; Kaitsuka et al, 2021 ).…”
Section: Pathophysiological Mechanisms That Lead To Agingmentioning
confidence: 99%
“…Sirtuin 2 (SIRT2) and nuclear factor erythroid 2-related factor 2 (NRF2), two direct targets of miR-140-5p, may strongly participate in oxidative stress in AS. The mechanistic role of SIRT2 in oxidative stress remains unclear as SIRT2 regulates hypoxia inducible factor 1 (HIF1) expression, but its positive regulation (stabilization) or negative regulation (degradation) is still debated [ 61 , 62 ]. In response to oxidative conditions, NRF2 is translocated into the nucleus, where it acts as a transcription factor activating anti-oxidative gene transcription [ 61 , 63 ].…”
Section: Role Of Mir-140-5p/-3p In Atherosclerosismentioning
confidence: 99%